European Integration After Amsterdam 2000
DOI: 10.1093/0198296401.003.0006
|View full text |Cite
|
Sign up to set email alerts
|

Executive Selection in the European Union: Does the Commission President Investiture Procedure Reduce the Democratic Deficit?

Abstract: Date of publication in the : 14.11.1997 | Full text | Back to homepage | Keywords IGC 1996, European Parliament, Commission, investiture procedure, executive accountability, Amsterdam Treaty, institutions, European elections, democracy, political science Abstract Central to all democratic systems is the ability of citizens to choose who holds executive power. To reduce the democratic-deficit in the EU, therefore, the Maastricht and Amsterdam Treaties give the European Parliament (EP) a vote on the European … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
14
0
2

Year Published

2002
2002
2017
2017

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 17 publications
(16 citation statements)
references
References 142 publications
0
14
0
2
Order By: Relevance
“…The challenge for empirical researchers is to measure individual-level perceptions of devolution and marry such data with a theoretical perspective on the development of a polity and notions of representation. Bradbury, 1998;Hazell and Cornes, 1999;Hazell, 2000;Laffin and Thomas, 1999;Laffin, Thomas and Webb, 2000;Marinetto 2001;McAllister, 2000aMcAllister, , 2000bRawlings, 1998;Webb, 1999. 2 See Katz, 2001;Tseblis and Garrett, 2000;McKay, 2000;Verdun, 1999;Elgie, 1999;Hix, 1997. 3 Further information on national identity will be available in late 2002 when the results of the 2001 Welsh Life and Times survey are released.…”
Section: Resultsmentioning
confidence: 99%
“…The challenge for empirical researchers is to measure individual-level perceptions of devolution and marry such data with a theoretical perspective on the development of a polity and notions of representation. Bradbury, 1998;Hazell and Cornes, 1999;Hazell, 2000;Laffin and Thomas, 1999;Laffin, Thomas and Webb, 2000;Marinetto 2001;McAllister, 2000aMcAllister, , 2000bRawlings, 1998;Webb, 1999. 2 See Katz, 2001;Tseblis and Garrett, 2000;McKay, 2000;Verdun, 1999;Elgie, 1999;Hix, 1997. 3 Further information on national identity will be available in late 2002 when the results of the 2001 Welsh Life and Times survey are released.…”
Section: Resultsmentioning
confidence: 99%
“…Indeed, a shift is evident in the structure of coalitions, towards one in which center-right coalitions are more common, while the fre-quency of "grand coalitions" of the EPP-PES has actually declined. This pattern was clearly discernible in the first six months of the 1999 Parliament, during which Hix (2000c) found that the "grand coalition" was evident in 60 percent of votes, as opposed to an average of 75 percent in the preceding parliament.…”
Section: The Rise Of Party Politicsmentioning
confidence: 92%
“…Hence, they put pressure on their MEPs to vote for the compromise, even if that implies voting against the line of their EP party group' (p. 845). Support for these arguments was found in studies analysing domestically sensitive votes such as the election of the EC president (Hix, 1997;Hix & Lord 1996), the enlargement process (Ö hlén, 2013), or the treaty reforms (Moravcsik, 1998).…”
Section: The European Parliament and The Euro Crisismentioning
confidence: 99%